2019
DOI: 10.2478/mjss-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Motives in Two Emerging Economies: A Comparison between Urban Mexico and Morocco

Abstract: This research tried to identify similarities and differences in motives between male urban entrepreneurs from Mexico and Morocco. The Mexican sample of 192 respondents was drawn from Chambers of Commerce listings in Guadalajara and Monterrey. The Moroccan sample of 222 respondents came from the Fès-Meknès region. In both countries a majority of entrepreneurs went into business by necessity and pursued monetary goals in order to secure their financial future for their families and for themselves. Larger cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The reviewed papers explore several motivations and challenges affecting entrepreneurial intentions. Motivating factors are a desire to enhance innovative capability (Mohammad et al , 2014; Rochdi et al , 2017; Golan-Nadir and Cohen, 2017; Al-Tarawneh, 2019), a need for achievement to gain self-satisfaction (Lagaras, 2017; Elali and Al-Yacoub, 2016; Alammari et al , 2019), a desire for financial security (Robichaud et al , 2019), a desire for social acceptance (Tausif and Haque, 2016) and the goal of promoting entrepreneurial knowledge and skills amongst young people (Gupta et al , 2012). Challenges include unemployment and socioeconomic inequalities (Ibtissem, 2019), a lack of access to long-term finance (Mohammadali and Abdulkhaliq, 2019), a lack of training on how to start a business (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed papers explore several motivations and challenges affecting entrepreneurial intentions. Motivating factors are a desire to enhance innovative capability (Mohammad et al , 2014; Rochdi et al , 2017; Golan-Nadir and Cohen, 2017; Al-Tarawneh, 2019), a need for achievement to gain self-satisfaction (Lagaras, 2017; Elali and Al-Yacoub, 2016; Alammari et al , 2019), a desire for financial security (Robichaud et al , 2019), a desire for social acceptance (Tausif and Haque, 2016) and the goal of promoting entrepreneurial knowledge and skills amongst young people (Gupta et al , 2012). Challenges include unemployment and socioeconomic inequalities (Ibtissem, 2019), a lack of access to long-term finance (Mohammadali and Abdulkhaliq, 2019), a lack of training on how to start a business (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Kirkeley (2016) investigated the role of values in entrepreneurial behaviour to find that the most important values among entrepreneurs are self-direction, ambition, creativity, and challenging the status quo. In the Mexican case, the main reason for starting a business is reaching financial independence, but also autonomy and personal development (Robichaud, Cachon, Taghzouti, Assaidi, & Codina, 2019). This study will evaluate the entrepreneur autonomy skill that has not been evaluated in Mexican social entrepreneurs.…”
Section: Social Entrepreneurshipmentioning
confidence: 99%
“…For example, Isaga et al [2] found that pull factors are more important for starting a business in developing countries than push factors. Other studies have shown that the motives vary by gender and country [3,4]. In most cases, this literature assumes that most successful entrepreneurs begin their entrepreneurial journey at a young age, while they are still energetic.…”
Section: Introductionmentioning
confidence: 99%